Pengaruh Viral Marketing, Promosi, dan Kualitas Pelayanan Terhadap Keputusan Pembelian MS Glow di Bumi Indah Kabupaten Tangerang - Evan Saktiendi; Septi Herawati; Lince Afri Yenny; Amelia Wahyu Agusti (PT FORMOSA CENDEKIA GLOBAL, 2022)
The purpose of this study was to determine the effect of viral marketing, promotion, and service quality partially and simultaneously on purchasing decisions for MS Glow in Bumi Indah, Tangerang Regency. The population in this study were MS Glow consumers in Bumi Indah, Tangerang Regency. The number of samples is 100 respondents using purposive sampling. The testing tool used is SPSS. The results of this study indicate that simultaneously viral marketing, promotion, and service quality variables have a significant effect on purchasing decisions for MS Glow in Bumi Indah, Tangerang Regency, while partially viral marketing and promotion variables have no significant effect on MS Glow purchasing decisions and service quality variables have an effect. significant impact on purchasing decisions for MS Glow in Bumi Indah, Tangerang Regency.